2016
DOI: 10.1371/journal.pone.0165968
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Associated Decline in Thymic Output Differs in Dog Breeds According to Their Longevity

Abstract: The age associated decline in immune function is preceded in mammals by a reduction in thymic output. Furthermore, there is increasing evidence of a link between immune competence and lifespan. One approach to determining thymic output is to quantify signal joint T cell receptor excision circles (sj-TRECs), a method which has been developed and used in several mammalian species. Life expectancy and the rate of aging vary in dogs depending upon their breed. In this study, we quantified sj-TRECs in blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 54 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…This may partly explain why anemia was not noted in WO animals ( -3) [21]. At this time, thymus function ceases in dog breeds [43]. This dramatic decline in hormesis at 10 years (Figure 3) indicates that the process is dependent on morphogenic cells that are of lymphocytopoietic origin.…”
Section: Discussionmentioning
confidence: 98%
“…This may partly explain why anemia was not noted in WO animals ( -3) [21]. At this time, thymus function ceases in dog breeds [43]. This dramatic decline in hormesis at 10 years (Figure 3) indicates that the process is dependent on morphogenic cells that are of lymphocytopoietic origin.…”
Section: Discussionmentioning
confidence: 98%
“…Since the formation of sj-TREC occurs specifically in the thymus and this DNA does not replicate, sj-TREC has been used as a biomarker for thymic output/RTEs in a wide range of species, including humans (Douek et al, 1998), mice (Sempowski et al, 2002), primates (Sodora et al, 2000), chickens (Kong et al, 1999) and pigs (Vallabhajosyula et al, 2011). In Labrador retriever dogs an ageassociated decline in sj-TREC values was observed which appear to be bi-phasic in nature, with differences occurring between different age groups, and has been previously described (Holder et al, 2016). This is similar to that seen in humans, where the greatest decline in sj-TRECs occur between the teenage years and middle age (40-50 years) (Geenen et al, 2003), subsequently, sj-TREC values show a slow decline between the 6 th and 9 th decades of life before decreasing significantly in the 10 th decade (Mitchell et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…The association between sj-TREC and IL7R genotypes also suggests a relationship between IL-7R expression and thymic involution. Human longitudinal studies have shown that sj-TREC values decline by an average of 3% of the baseline level per year (Kilpatrick et al, 2008), while a recent study in dogs suggests that differences in sj-TREC levels observed between individual young Labrador retrievers might be indicative of the rate of thymic involution (Holder et al, 2016). In mouse strains which undergo rapid thymic involution, as determined by an earlier decline in sj-TREC values, developing thymocytes were found to have increased expression of IL-7R, compared to those mouse strains demonstrating a slower rate of thymic involution (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations